2012
DOI: 10.1158/1078-0432.ccr-11-3293
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Stem Cell Reinfusion and Escalated Dose Melphalan in Castration-Resistant Prostate Cancer: A Phase 1 Study

Abstract: Purpose: Nontaxane-based chemotherapeutic options in castrate-resistant prostate cancer (CRPC) are limited despite the long natural history of the disease. We carried out a phase 1 dose-escalation study of the alkylating agent melphalan with autologous stem cell transplantation, comparing rapid changes in circulating tumor cells (CTC) and prostate-specific antigen (PSA) as a measure of response.Experimental Design: Cohorts of individuals with advanced CRPC received high-dose intravenous melphalan, and autologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…24 However, the CellSearch system has been shown to be the most reliable tool in clinical trials using CTCs as a prognostic marker. [25][26][27][28][29][30] Limitations to this method and the functional significance of detected CTCs are further discussed in the eAppendix in the Supplement.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, the CellSearch system has been shown to be the most reliable tool in clinical trials using CTCs as a prognostic marker. [25][26][27][28][29][30] Limitations to this method and the functional significance of detected CTCs are further discussed in the eAppendix in the Supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with conversion experienced a higher response rate and a longer median time on study; the reported results strongly suggest the prognostic role of CTC assessment. Shamash and colleagues [79] evaluated the clinical benefit of high doses of the alkylating agent melphalan in CRPC patients and found that patients who experienced a CTC count drop below 5/7.5 ml had a significantly longer OS (30.6 vs. 15.3 months; p = 0.03); very interestingly, the CTC conversion happened within 2 weeks from the beginning of the therapy and faster than a concomitant PSA decline, suggesting that CTC evaluation could be helpful to promptly target such a toxic approach only to CTC-responding patients. Most recently, Goldkorn et al [80] prospectively analyzed the prognostic value of CTC enumeration in 212 evaluable CRPC patients receiving first-line docetaxel-based therapy within a large phase III clinical trial (SWOG S0421).…”
Section: Role Of Ctcs In the Clinical Management Of Pc Patientsmentioning
confidence: 99%
“…Meanwhile, in a study of patients with CRPC, post-treatment CTC numbers were a stronger prognostic factor for survival than a 50% decline in PSA (receiver operating characteristic area under the curve: 0.87 vs 0.62), and the authors suggested that CTC numbers measured at 4 or 8 weeks can even discriminate between favorable or unfavorable outcomes with therapy [60]. Decrease of number of CTCs after chemotherapy for CRPC patients was also observed correlated with better survival in a Phase I study [96]. In metastatic colorectal cancer patients, a conversion of baseline unfavorable CTC number to a favorable one at 3-5 weeks after treatment was reported to be correlated with significant longer survival compared to those without this change [77].…”
Section: Biomarkers In Monitoring Treatment Responsementioning
confidence: 98%